Aapasuon kasvillisuus ja sen vaikutus hiilidioksidin vaihtoon - Hyvönen, Hanna (Helsingfors universitet, 2015)
Northern aapa mires are important carbon sinks. Their CO2 exchange with the atmosphere is based on plant photosynthesis and respiration, and the decomposition of peat and other dead organic matter by microbial activity. The photosynthetic efficiency of plants depends on environmental factors and the amount and development of plant leaf area and biomass. There is not much research on the leaf area index and biomass of plants on aapa mires which makes them an interesting and important subject of research. This study investigated plant community composition, development and their effect on CO2 exchange at a northern aapa mire in Finland. The purpose of this study was to survey the biomass and leaf area index of plants within mire types and determine how they, together with water level and microbial activity, and explain the CO2 exchange between the mire and atmosphere. Another aim of this study was to construct regression models for predicting biomass and leaf area index using the plants height and coverage data. The study was conducted in summer 2014 at Halssiaapa, an aapa mire in Sodankylä. The mire was divided into oligotrophic, mesotrophic and eutrophic hummocks, lawns and hollows. The plant community species, their height and coverage were determined in early June, mid-July and mid-August. Moreover, the growth of plant groups was monitored weekly at 16 inventory squares between 6th June and 18th August. Biomass and leaf area samples were collected from different mire types in mid-July, and by the use of regression analysis, two equations were modelled for each plant group, one for predicting biomass and another for predicting leaf area index. The equations were used for predicting biomass and leaf area index for plant groups and mire types based on early June and mid-August data, and the weekly inventory squares. CO2 exchange, and factors controlling it, were measured via an eddy covariance method (measures exchange at ecosystem scale), and a closed chamber method (measures exchange from 1m2). Biomass, leaf ...